Women's Representation In Village Deliberations Regarding Determination Of Development Direction In Laut Dendang Village, Deli Serdang Regency: Keterwakilan Perempuan Dalam Musyawarah Desa Terkait Penetapan Arah Pembangunan Di Desa Laut Dendang Kabupaten Deli Serdang - Anisa Putri; Dewi Wulandari; Elisman Pangondiyan Siregar; Julia Ivanna (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This study aims to analyze women's representation in village deliberations related to determining development directions in Laut Dendang Village, Deli Serdang Regency. The study used a descriptive qualitative method with a field research approach. Data were obtained through observation and in-depth interviews with the Village Secretary and female members of the Village Consultative Body (BPD). Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. While data validity was tested through source and technique triangulation. The results show that women have been involved in the Village Development Planning Deliberation (Musrenbangdes) with an attendance rate of around 34%–36% of total meeting participants. However, strategic positions in the village government and BPD are still dominated by men. Factors influencing women's involvement include village government support, formal invitation systems, women's social groups, and obstacles such as work schedule conflicts and domestic responsibilities. Women also contribute to development proposals in the areas of public health and social empowerment. However, village budget allocations still focus more on physical development than on community empowerment. Thus, women's representation in village deliberations has been formally demonstrated, but their involvement in strategic decision-making remains limited.